2011
DOI: 10.1159/000335000
|View full text |Cite
|
Sign up to set email alerts
|

Enrollment in Clinical Trials Correlates with Improved Survival in Metastatic Melanoma

Abstract: Background: Although the current median survival time of stage-IV melanoma patients is less than 12 months, there is a subset of patients who experience long-term survival. Due to poor response rates to standard cytotoxic agents in metastatic melanoma, patients are encouraged to participate in clinical trials, the overall impact of which has not been studied, however. The aim of our study was to identify the factors associated with long-term survival and to determine the impact of clinical trial enrollment on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…Although interferon alfa-2b is currently the only FDA-approved systemic adjuvant therapy for melanoma, several other immunotherapies are currently being evaluated in clinical trial settings, some of which have shown promise [13]. In this regard, our group has previously reported that for metastatic patients, enrollment in clinical trials correlates with improved survival [14]. Of note, of twenty-three patients in our cohort receiving adjuvant therapy through clinical trials, only one of these patients was in the older age group, despite the fact that none of the protocols had an upper age limit for enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…Although interferon alfa-2b is currently the only FDA-approved systemic adjuvant therapy for melanoma, several other immunotherapies are currently being evaluated in clinical trial settings, some of which have shown promise [13]. In this regard, our group has previously reported that for metastatic patients, enrollment in clinical trials correlates with improved survival [14]. Of note, of twenty-three patients in our cohort receiving adjuvant therapy through clinical trials, only one of these patients was in the older age group, despite the fact that none of the protocols had an upper age limit for enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…Είναι γνωστό ότι η ρυθμικότητα έκκρισης της λεπτίνης σε υγιή άτομα εξαφανίζεται σε παρατεταμένη νηστεία258 και πιθανότατα η ινσουλίνη να παίζει σημαντικό ρόλο σε αυτή τη ρύθμιση, αλλά εξίσου πιθανό είναι το μελάνωμα να επηρεάζει τη ρυθμικότητα στην έκκριση της λεπτίνης και τον έλεγχο της ινσουλίνης σε αυτή. Τέλος, έχει αναφερθεί στη διεθνή βιβλιογραφία ότι οι συμμετέχοντες σε κλινικές μελέτες εμφανίζουν καλύτερη επιβίωση σε σχέση με ασθενείς που δεν συμπεριλαμβάνονται σε κλινικές μελέτες259 , και ίσως αυτό το γεγονός επηρέασε τα αποτελέσματα ως συγχυτικός παράγοντας.Σε μια in vitro μελέτη έχει καταδειχθεί ότι η λεπτίνη μπορεί να προάγει την ανάπτυξη μελανωματικών κυττάρων όταν χορηγείται εξωγενώς260 πιθανότατα μέσω μηχανισμών νέοαγγειογένεσης, αλλά παράλληλα διαπιστώθηκε ότι η ανάπτυξη του όγκου δεν απαιτεί την παρουσία της λεπτίνης του ξενιστή, αφού τα πειραματόζωα δεν είχαν αυξημένη λεπτίνη ορού και εμφάνισαν περαιτέρω ανάπτυξη του μελανώματος τους μόνο με τη χορήγηση λεπτίνης, γεγονός που συμβαδίζει με τα αποτελέσματα της μελέτης επιβίωσης. Στην ίδια εργασία διαπιστώθηκε ότι η παχυσαρκία -και όχι η λεπτίνη -καθορίζει την αύξηση του μεγέθους του όγκου και ότι η έλλειψη λεπτίνης σε μη παχύσαρκα πειραματόζωα σχετιζόταν με ελάττωση της αύξησης του όγκου.Συνεπώς μπορούμε να υποθέσουμε ότι η λεπτίνη παίζει ίσως κάποιο ρόλο στην εμφάνιση του μελανώματος σε συνδυασμό με την παχυσαρκία, αλλά μόλις εμφανιστεί πλέον το μελάνωμα η λεπτίνη του ξενιστή δεν φαίνεται να παίζει κάποιο ρόλο σε σχέση με την επιβίωση του ασθενούς.Το ενδιαφέρον επίσης στη μελέτη της Brandon ήταν ότι οι ποντικοί που έπαιρναν δίαιτα χαμηλή σε θερμίδες -και είχαν συνεπώς αυξημένη λεπτίνη -εμφάνιζαν συρρίκνωση του όγκου.Με βάση τα μέχρι τώρα βιβλιογραφικά δεδομένα δεν υπάρχει μελέτη επιβίωσης σε ασθενείς με μελάνωμα στον ελληνικό ή σε άλλο πληθυσμό που να έχει ελέγξει τις παραμέτρους της τρέχουσας μελέτης.…”
unclassified